A curved 2.5D model for simulating dynamic responses of coupled track-tunnel-soil system in curved section due to moving loads. (7th July 2019) - Ma, Longxiang; Ouyang, Huajiang; Sun, Chang; Zhao, Ruitong; Wang, Le
Abstract: Ground-borne vibration excited by railway traffic has attracted much research in very recent years and its conventional three-dimensional numerical analysis is known to be tedious and time consuming. Advanced numerical models based on a significant model reduction which can simulate this problem in an efficient way have been developed only for straight railway lines. To achieve a significant reduction of the number of degrees-of-freedom in the determination of dynamic responses of a coupled curved track-tunnel-soil system due to moving loads, a curved two-and-a-half-dimensional (2.5D) model is presented in this paper. In this model, the track-tunnel-soil system is assumed to be invariant in the longitudinal direction. Further, a curved 2.5D finite element method is proposed to model the tunnel-soil system and provide an appropriate artificial boundary of the computation domain, while a 2.5D analytical method considering the longitudinal, transverse, vertical and rotational motions of the rail is developed to model the curved track. By exploiting the force equilibrium and displacement compatibility conditions, the curved track with an analytical solution is coupled to the curved tunnel-soil system with a finite element solution, leading to the governing equation of motion of the whole curved track-tunnel-soil system. Through comparisons with other theoretical models, the proposed model is validated. Numerical examples show that the proposed model can efficiently simulate the dynamic responses of the curved track-tunnel-soil system due to its significant advantage that the discretization and solution are required over only the cross section. Some interesting dynamic phenomena of the curved track-tunnel-soil system subjected to generalized moving loads acting on the rail are also found through the numerical analyses. Highlights: A curved 2.5D approach is proposed to model the curved track-tunnel-soil system. The formulations of the curved 2.5D finite elements are presented. All related motions of the curved track are considered. Some peculiar dynamic phenomena of the curved track-tunnel-soil system are found.